2022
DOI: 10.1016/j.redox.2021.102219
|View full text |Cite
|
Sign up to set email alerts
|

A new FGF1 variant protects against adriamycin-induced cardiotoxicity via modulating p53 activity

Abstract: A cumulative and progressively developing cardiomyopathy induced by adriamycin (ADR)-based chemotherapy is a major obstacle for its clinical application. However, there is a lack of safe and effective method to protect against ADR-induced cardiotoxicity. Here, we found that mRNA and protein levels of FGF1 were decreased in ADR-treated mice, primary cardiomyocytes and H9c2 cells, suggesting the potential effect of FGF1 to protect against ADR-induced cardiotoxicity. Then, we showed that treatment with a FGF1 var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Upstream of SIRT1, in addition to miRNAs, a novel fibroblast growth factor 1 variant could counteract adriamycin-induced apoptosis by decreasing p53 activity via upregulation of SIRT1-mediated p53 deacetylation. 235 There have also been a series of studies on the antiapoptotic effect of melatonin which regulates SIRT1 in various physiological processes. [236][237][238][239] Additionally, some chemicals or drugs, like cambinol and ginsenoside Rc, have been shown to inhibit or activate SIRT1 to regulate the apoptotic process.…”
Section: The Regulatory Role Of Sirts In Cellular Biologymentioning
confidence: 99%
“…Upstream of SIRT1, in addition to miRNAs, a novel fibroblast growth factor 1 variant could counteract adriamycin-induced apoptosis by decreasing p53 activity via upregulation of SIRT1-mediated p53 deacetylation. 235 There have also been a series of studies on the antiapoptotic effect of melatonin which regulates SIRT1 in various physiological processes. [236][237][238][239] Additionally, some chemicals or drugs, like cambinol and ginsenoside Rc, have been shown to inhibit or activate SIRT1 to regulate the apoptotic process.…”
Section: The Regulatory Role Of Sirts In Cellular Biologymentioning
confidence: 99%
“…Multiple works identified that fibroblast growth factor 1 (FGF1) is elevated by oxidative damage, implying that an increased FGF1 expression is an adaptive response and might be protective under different kinds of stresses. Our previous study revealed that FGF1 displayed therapeutics and favorable effects on maintaining myocardial redox homeostasis and improving cardiac function, especially in the setting of DOX treatment [ 8 , 9 ]. Beyond that, FGF1 is now emerging as possessing various protective effects including but not restricted to promoting angiogenesis [ 10 ] and alleviating apoptosis [ 11 ] and fibrosis [ 9 ] through partly attenuating oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that FGF1 displayed therapeutics and favorable effects on maintaining myocardial redox homeostasis and improving cardiac function, especially in the setting of DOX treatment [ 8 , 9 ]. Beyond that, FGF1 is now emerging as possessing various protective effects including but not restricted to promoting angiogenesis [ 10 ] and alleviating apoptosis [ 11 ] and fibrosis [ 9 ] through partly attenuating oxidative stress. These findings support the idea that FGF1 has a great potency in the prevention and treatment of heart injury in response to stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Conditional cardiac-specific HUWE1 (a ubiquitin E3 ligase) knockout mice developed cardiac hypertrophy, accompanied by impaired mitochondrial energy metabolism and ROS defense [ 85 ]. The reversal of murine double minute 2 (MDM2), a p53-specific E3 ubiquitin ligase, and SIRT1 reduced the activity of the apoptosis factor p53 through SIRT1-mediated p53 deacetylation and MDM2-mediated p53 ubiquitination, which alleviated oxidative stress and cell apoptosis in the tissues and cells of a cardiomyopathy model induced by adriamycin [ 86 ].…”
Section: Interaction Of the Ups And Oxidative Stress In Cvdsmentioning
confidence: 99%